Struggle over th pie? The gendered distribution of power and subjective financial well-being within UK households - Jerome De Henau; Susan Himmelweit (The Open University, Economics Department, 2007)
This paper investigates the ways in which the distribution of power and well-being within couple households is gendered in the sense of having gendered determinants, from inside the household, rather than just gendered outcomes. We model such households, as Sen (1990) suggests, as sites of cooperative conflict, where decision-making has a component reflecting shared views and a component representing a bargain over conflicting views. Using household panel data from the British Household Panel Survey (1996-2003), in which individual answers can be matched across couples, the method takes answers to a question about financial satisfaction to be indicators of (i) the level of current and potential resources of the household, and (ii) intra-household bargaining over the entitlement each individual has to these resources. Individual financial satisfaction can then be decomposed into two elements; the first, the average of a couple's satisfaction scores, represents their shared view; the second is the difference between their answers. Stripping out the effects of unobserved heterogeneity through the use of fixed effects panel methods and carefully chosen controls, the effect of explanatory factors on this difference can then be identified as the result of a perceived difference in entitlements to household income that is the result of unequal power between male and female partners. Our results suggest the co-existence of shared and conflicting views, with a significant gendered pattern. Some policy implications are also discussed.
Keywords: D13; D60; J16; 330; gender differences; household bargaining; income satisfaction; subjective well-being; collective models; perceived contribution; financial autonomy; Geschlechterdiskriminierung; Haushaltseinkommen; Zufriedenheit; Soziale Lage; Frauen; Entscheidung; Privater Haushalt; Schätzung; Großbritannien